DEVELOPMENT OF DIGITAL MODULE FOR ELECTRIC VEHICLE CONVERSION (ATIKANOTO: Journal of Automotive Engineering Education, 2024)
The Indonesian government strongly supports the conversion of fuel-based vehicle drive systems to electric motorbikes. The convenience obtained due to the conversion of this vehicle receives subsidies from the government in the form of incentives or discounted financial assistance. Few citizen in Indonesia not understand what spare parts are used, what specifications should be used. Based on this, the development of a digital electric vehicle conversion module is necessary, because during the current transition period for fuel oil vehicles to electricity, there are still no conversion books/modules available. This research uses research and development methods or design research and development (RD) which involves a 4D model (definition, design, development and dissemination). The participants in this research were 5 media expert validators and 4 media expert validators to validate the feasibility of developing a digital module for electric vehicle conversion. The research results showed that the digital module structure consists of the initial part, namely the digital module cover, digital module identity sheet, table of contents, and foreword. The content section is the cover of the sub-material, the cover of the sub-chapter of the material, and the description of the material. The final part is the bibliography and author biography. The contents of this digital electric vehicle conversion module include material related to electric vehicles, namely electric vehicles, history of electric vehicles, components (electric motor, controller, battery and onboard charger), electric vehicle conversion and safety. This digital module, seen from a media and meta perspective, is said to be "Very Appropriate". Pemerintah Indonesia sangat mendukung terkait konversi sistem penggerak kendaraan berbasis bahan bakar menjadi motor Listrik. Selain itu kemudahan yang didapat dikarenakan konversi kendaraan ini mendapatkan subsidi dari pemerintah berupa insentif ataupun bantuan dana potongan. Kekurangannya yaitu dimana sumber daya manusia (SDM) di Indonesia masih sedikit yangg mengerti terkait sparepart apa saja yang digunakan, spesifikasi apa yang seharusnya dipakai. Berdasarkan hal tersebut pengembangan modul digital konversi kendaraan listrik diperlukan, dikarenakan pada masa transisi kendaraan bahan bakar minyak ke listrik seperti saat ini masih belum ada buku/modul konversi yang tersedia. Penelitian ini menggunakan metode penelitian dan pengembangan atau desain penelitian dan pengembangan (RD) yang melibatkan model 4D (definisi, desain, pengembangan, dan diseminasi). Partisipan dari penelitian ini yaitu 5 orang validator ahli media dan 4 orang validator ahli media untuk memvalidasi kelayakan dari pengembangan modul digital konversi kendaraan listrik. Hasil penelitian didapatkan bahwa struktur modul digital terdiri dari bagian awal yaitu sampul modul digital, lembar identitas modul digital, daftar isi, dan kata pengantar. Bagian isi yaitu sampul sub materi, sampul sub bab materi, dan uraian materi. Bagian akhir yaitu daftar pustaka dan biografi penulis. Isi dari modul digital konversi kendaraan listrik ini yaitu materi terkait kendaraan listrik yaitu kendaraan listrik, sejarah kendaraan listrik, komponen – komponen (motor listrik, kontroler, baterai, dan On board charger), konversi kendaraan listrik, dan safety. Modul digital ini dilihat dari segi media dan metari dikatakan ”Sangat Layak”.